Pspice modelling and simulation of a matrix converter-fed induction motor drive - Tatar, Y; Sünter, S (Springer-Verlag, 2002)
In this paper, a three-phase-in three-phase-out matrix converter induction motor drive is modelled using the Pspice software package. Semiconductor devices each with its snubber circuit are also modelled to demonstrate the switching behaviour of the devices in the converter. A small L-C filter at the input side of the converter is used to remove distortion of the input current around the switching frequency. The input filter and the induction. motor are also included in the Pspice model. The simulation results obtained from the model at various operating conditions are presented.
Keywords: matrix converter; pspice modelling; induction motor; simulation